2010
DOI: 10.1089/ars.2009.2883
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Functions of Selenoprotein M and its Role in Cytosolic Calcium Regulation

Abstract: Selenoproteins contain the trace element selenium incorporated as selenocysteine, the 21 st amino acid. Some members of the selenoprotein family, such as the glutathione peroxidases, have well-characterized antioxidant activity, functioning in enzymatic breakdown of hydroperoxides to protect cells against oxidative stress. However, the functions of many of the 25 human selenoproteins, including the brain-enriched selenoprotein M, are unknown. We investigated selenoprotein M function by manipulating expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 35 publications
5
86
0
2
Order By: Relevance
“…In addition, Sep15 has been implicated in preventing liver (192), prostate (147), breast (264), and lung cancers (8). However, other studies demonstrated a role of Sep15 in promoting some types of cancer including colon cancer (153,347 (294). However, the exact function of SelM and its physiological roles in the brain as well as in other tissues remain unclear.…”
Section: H the 15-kda Selenoprotein And Selenoprotein Mmentioning
confidence: 99%
“…In addition, Sep15 has been implicated in preventing liver (192), prostate (147), breast (264), and lung cancers (8). However, other studies demonstrated a role of Sep15 in promoting some types of cancer including colon cancer (153,347 (294). However, the exact function of SelM and its physiological roles in the brain as well as in other tissues remain unclear.…”
Section: H the 15-kda Selenoprotein And Selenoprotein Mmentioning
confidence: 99%
“…After 24 h, cells were lysed, an aliquot of the whole cell lysate stored at Ϫ20°C, and remaining whole cell lysates were incubated with 15 l of protein-A Dynabeads (Invitrogen) with 10 g of prebound monoclonal anti-SelK for 2 h to immunoprecipitate SelK. The beads were washed and incubated at 95°C for 10 min in laemmli buffer and autoradiography performed as previously described (17). HEK293 cells were transfected with this plasmid or empty control plasmid using Lipofectamine 2000 (Invitrogen) for 24 h before lysis and analysis for protein expression.…”
Section: Preparation Of Ex Vivo Cells and Bmdm-purification Of T Cellmentioning
confidence: 99%
“…In PD pathology not only Se-dependent antioxidative enzymes are affected; both the level and activity of other enzymes related to the GSH metabolism are also changed. Increased expression of glutathione Stransferase (GST), which is a major enzyme involved in the regulation of oxidative stress, was observed in SN as well as in cerebrospinal fluid from PD patients [150][151][152].…”
Section: Parkinson's Diseasementioning
confidence: 99%